Flap Advancement Technique for Scalp Hair Preservation in Massive Cutis Verticis Gyrata - Bilal Javed; Amina Rao; Waleed Abdullah; Akasha Amber; Mughese Amin (Indian Journal of Plastic Surgery)
Cutis verticis gyrata (CVG) is a rare skin condition characterized by ridges and furrows resembling the brain. CVG falls under three categories: primary essential, primary nonessential, and secondary. This case report focuses on primary essential CVG, where approximately a fourth of the scalp and a significant portion of the forehead and eyelid were involved.